ANALISIS KEBUTUHAN PENGEMBANGAN PERANGKAT PEMBELAJARAN KIMIA DASAR BERBASIS INKUIRI - Suardana, I Nyoman; Juniartina, Putu Prima (Jurnal Pendidikan Matematika dan IPA, 2020)
The research aimed to need analysis of developing Basic Chemistry learning tools based on inquiry. This was descriptive research. The subjects were a syllabus, two lectures, and 43 students of the Third Semester in Academic Year 2018/2019 on Science Education Study Program, Ganesha University of Education. The object was Basic Chemistry topics, the materials that are difficult for the students and their cause, lectures constraint in learning, and lectures view about learning based on inquiry. Data were collected by questionnaire and documentation. Data were analyzed by descriptively. The result showed that the Basic Chemistry topics include: material and its' change, atomic structure, periodic system of elements, chemical bonding and molecular structure, stoichiometry, thermochemistry, chemical kinetics, chemical equilibrium, acid and base, hydrolysis, buffer, colligative properties, colloid, redox and electrochemistry, elemental chemistry, and organics chemistry. All of the topics were considered difficult by a certain number of students. Most of student difficulties were found in the topics: stoichiometry, chemical kinetics, and colligative properties (58.14%), but the smallest in the topics: material and its' change, and atomic structure (13.95%). The students’ difficulties are caused by the abstract materials (23.26%), low of mathematics ability of students (34.88%), the students learning only for doing task/test (59.53%), low students’ prior-knowledge (46,51%), the students, habit to memorizing learning (51,16%), the students did not reflect their learning (53,48%), and the students easily forget the concepts learned (65,12). The lectures constraint in learning comprises designing and implementing of learning and assessment. The lectures said that the Basic Chemistry learning tools based on inquiry are important to be developed to facilitate the students in constructing the knowledge.AbstrakPenelitian ini bertujuan memerlukan analisis pengembangan alat pembelajaran Kimia Dasar berdasarkan inkuiri. Ini adalah penelitian deskriptif. Subjek penelitian adalah silabus, dua kuliah, dan 43 mahasiswa Semester Ketiga Tahun Akademik 2018/2019 tentang Program Studi Pendidikan Ilmu Pengetahuan, Universitas Pendidikan Ganesha. Objeknya adalah topik Kimia Dasar, materi yang sulit bagi siswa. Data penelitian dikumpulkan melalui kuesioner dan dokumentasi. Data dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa topik Kimia Dasar meliputi: bahan dan perubahannya, struktur atom, sistem periodik elemen, ikatan kimia dan struktur molekul, stoikiometri, termokimia, kinetika kimia, keseimbangan kimia, asam dan basa, hidrolisis, penyangga, sifat koligatif , koloid, redoks dan elektrokimia, kimia unsur, dan kimia organik. Semua topik dianggap sulit oleh sejumlah siswa. Sebagian besar kesulitan siswa ditemukan dalam topik: stoikiometri, kinetika kimia, dan sifat koligatif (58,14%), tetapi yang terkecil dalam topik: materi dan perubahannya, dan struktur atom (13,95%). Kesulitan siswa disebabkan oleh materi abstrak (23,26%), rendahnya kemampuan matematika siswa (34,88%), siswa belajar hanya untuk mengerjakan tugas / tes (59,53%), rendahnya pengetahuan awal siswa (46,51) %), siswa, kebiasaan menghafal pembelajaran (51,16%), siswa tidak mencerminkan pembelajarannya (53,48%), dan siswa mudah melupakan konsep yang dipelajari (65,12). Kendala kuliah dalam pembelajaran terdiri dari perancangan dan implementasi pembelajaran dan penilaian. Dosen yang merupakan subjek penelitian menyatakan bahwa alat pembelajaran Kimia Dasar berdasarkan penyelidikan adalah penting untuk dikembangkan guna memfasilitasi siswa dalam membangun pengetahuan.Kata Kunci: analisis kebutuhan, kimia dasar, inkuiri, kesulitan belajar, kendala belajar